The International Encyclopedia of Media Psychology 2020
DOI: 10.1002/9781119011071.iemp0160
|View full text |Cite
|
Sign up to set email alerts
|

Media Use and Materialism

Abstract: Research studies indicate that media use can contribute to the development of audience materialism. Primarily guided by cultivation analysis, social learning, and social comparison theory, the studies of media use and materialism began with concerns about the influence of television on viewers' materialistic values. With the change in media consumption shifting to be more personalized and selective in recent years, research has turned to study the effects of media celebrities and specific media content such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Taken together, the findings obtained in the current study contribute to a confirmation of the SOS-T [13]. Facebook seems to attract vulnerable narcissists due to several features it provides, including comparison with others in a hidden manner, communication in a controlled environment, and, more generally speaking, to self-regulation; this is consistent with former empirical findings [14,15]. Vulnerable narcissists seem to employ features of SNSs for self-regulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Taken together, the findings obtained in the current study contribute to a confirmation of the SOS-T [13]. Facebook seems to attract vulnerable narcissists due to several features it provides, including comparison with others in a hidden manner, communication in a controlled environment, and, more generally speaking, to self-regulation; this is consistent with former empirical findings [14,15]. Vulnerable narcissists seem to employ features of SNSs for self-regulation.…”
Section: Discussionsupporting
confidence: 90%
“…More specifically, Facebook seems to serve as a means to reach multiple self-regulatory goals, such as increasing self-esteem, presenting oneself, or interacting with others. Even though more work is needed in this respect, empirical evidence supports SOS-T: Several studies [ 14 , 15 ] demonstrated that both for users high in materialism, i.e., a personality facet triggering the idea that acquiring possession leads to happiness [ 16 ], and for those high in VN, Facebook seems to serve as a means to self-regulation.…”
Section: Introductionmentioning
confidence: 99%